ORIENTASI TUJUAN SISWA SMK KESEHATAN GRIYA HUSADA SUMBAWA BERDASARKAN INDEKS PRESTASI - Dirga Sesi Dwi Putra; Muhammad Irham; Rizky Fadillah (REALISTIC: Journal of Education Mathematics and Science, 2023)
Goal orientation is one way to find out which students are suitable for what method. students with a mastery goal orientation view success as an increase in self-efficacy, while students with a performance goal orientation view success through comparison with others. This study aims to compare the learning achievement of students of SMK Kesehatan Griya Husada based on goal orientation. Research is quantitative research. The population and sample in this study amounted to 25 students. Data was collected through tests and questionnaires. The data analysis used descriptive statistics and homogeneous t-test. The results of this study indicate that the average learning achievement of students with mastery orientation is 78.94 with the highest score of 85 and the lowest of 70. The average learning achievement of students with performance orientation is 78.25 with the highest score of 85 and the lowest score of 75. t Homogeneity gives the result t_hitung=3.78020556>t_tabel=2.064 which means H1 is accepted so it can be concluded that the average mastery-oriented student learning achievement is greater than the average performance-oriented student learning achievement.